Bone marrow mesenchymal stem cells decrease CHOP expression and neuronal apoptosis after spinal cord injury. (1st January 2017) - Gu, Chuanlong; Li, Heyangzi; Wang, Chao; Song, Xinghui; Ding, Yuemin; Zheng, Mingzhi; Liu, Wei; Chen, Yingying; Zhang, Xiaoming; Wang, Linlin
Highlights: Traumatic injury increased CHOP expression and apoptosis in rat spinal cord. BMSCs transplantation decreased CHOP expression, apoptosis, and increased the locomotor function. Co-culture with BMSCs decreased OGD induced CHOP expression and apoptosis in motor neurons. Co-culture with BMSCs-CM restored the viability of post-OGD motor neurons. Abstract: Spinal cord injury (SCI) leads to irreversible neuronal loss and ultimately leads to paralysis. Bone marrow derived mesenchymal stem cells (BMSCs) have been demonstrated to be an effective approach to treat SCI. The present study was designed to investigate the role of BMSCs in rats with spinal cord injury and in oxygen-glucose deprivation (OGD) treated motor neurons. The results demonstrated that BMSCs could improve locomotor function and decrease expression of pro-apoptotic transcription factor C/EBP homologous protein (CHOP) and apoptosis after SCI. Furthermore, co-culture with BMSCs or conditioned medium from BMSCs could also decrease the expression of CHOP and apoptosis in post-OGD motor neurons, supporting that BMSCs exerts protective effects by decreasing the expression of CHOP in injured motor neurons. Our findings provide a potential novel mechanism for BMSCs treatments in patients with SCI.